Cytotoxicity and Membrane Interaction of Tamoxifen as Affected by Ca2+ and Mg2+: Use of a Bacterial Model System - Luxo, C. (1999)
A strain of Bacillus stearothermophilus was used as a model to study the interaction of tamoxifen (TAM) with the membrane and the cytostatic antiproliferative effects not related to estrogen binding. TAM inhibits the growth of B. stearothermophilus as a function of concentration. The supplementation of the growth medium with Ca2+ or Mg2+ partially relieves the growth inhibition by TAM, allowing growth at TAM concentrations that fully impair growth in the basal medium. Fluorescence polarization of 1,6-diphenyl-1,3,5-hexatriene (DPH) and of its propionic acid derivative (DPH-PA) reveals opposite effects induced by TAM and Ca2+. The addition of Ca2+ to liposomes of bacterial lipids promoted physical ordering as opposed to disordering induced by TAM. Thus, it is predictable that growth impairment induced by TAM is mediated through perturbations at the membrane level.